Klong yao and the Performance of Minority Identity in the Siamese Community of Perlis, Malaysia - Tassanawongwara, Chayuti; Hussin, Hanafi (Malaysian Journal of Music, 2019)
The klong yao performance in the Siamese communities of Perlis was adopted from the Thai community in Central Thailand. Before this adoption, the ethnic consciousness of the Siamese communities was oriented towards a local variation of Thai-ness with similarities to southern Thai people in terms of linguistic and geopolitical references. After the klong yao was actively included in their cultural practices, the Siamese communities began to develop a representative identity that reinforced Central Thai cultural expressions. In this respect, the performance of klong yao reconstructs the identity of the Siamese communities in Perlis, Malaysia toward a Central Thai identity. The shift from a local and marginalised type of Siamese identity to a hegemonic and centralised Thai identity is observed with the choice to use klong yao as a representation of their identity during Malaysia’s various occasions for showcasing cultural performances.